Problems Detection in Urinary Tract of Dogs Using Ultrasound Method - I Putu Gede Yudhi Arjentinia; Putu Ayu Sisyawati Putriningsih (Journal of Veterinary and Animal Sciences, 2017)
The aim of this study was to detect urinary tract problem in dogs using ultrasonography method as a diagnostic supporting tool. Two-dimensional ultrasonography was used for examination of 40 dogs. The diagnosis was confirmed by the alteration of shape, size, position and echogenicity of the renal. Abnormalities on renal were extension of medulla, urolithiasis, and renal atrophy. The extension of medulla was indicated by medulla and pelvis dilatation, also disappearance of renal parenchyma. Sonograms of renal urolithiasis were shown by hyperechoic mass with acoustic shadowing. Narrowing of medulla and disappearance of cortex structure were the characteristics of renal atrophy sonogram. Abnormalities in vesical urinary and urethra were cystitis, urolithiasis, and urethral urolith obstruction, respectively. Ultrasonography utilization as diagnostic supporting tool for the urinary organ abnormalities in dogs generating a high accuracy diagnosis.